Methodology for synthesizing the nickel cobalt hydroxide/oxide and reduced graphene oxide complex for energy storage electrodes. (December 2017) - Yang, Sheng-Sian; Lin, Lu-Yin; Li, Xin; Ma, Cheng-Wei; Lai, He-Xin; Lin, Lu-Ying
Graphical abstract: Highlights: Reduced graphene oxide and nickel cobalt compound is synthesized on nickel foam. The low-cost and simple hydrothermal reaction is the mostly used synthesis method. Three different methodologies relating to the hydrothermal reaction are compared. Hydrothermal steps, direct/indirect growth, post-thermal treatment are compared. Highest CF of 5.61 F/cm 2 corresponding to capacity of 1.24 mAh/cm 2 is achieved. Abstract: Reduced graphene oxide (RGO) and nickel cobalt hydroxide/oxide complex is one of the promising electrocapacitive materials for the energy storage devices, in which RGO provides high conductivity and nickel cobalt hydroxide/oxide possesses high electrochemical activity toward conducting multiple Faradic reactions. The low-cost and simple hydrothermal reaction is the mostly used synthesis method for preparing the RGO and nickel cobalt hydroxide/oxide nanomaterials on the nickel foam. However, the methodologies based on the hydrothermal reaction are barely discussed in considering of the morphology of the nanomaterial and the electrochemical performance of the energy storage electrodes. The methodology includes the one-step and two-step hydrothermal reactions, direct growth and indirect deposition of the electroactive material on the nickel foam, and the post-thermal treatments. The highest specific capacitance value of 5.61 F/cm 2 corresponding to the capacity of 1.25 mAh/cm 2 are achieved for the nickel cobalt oxide and RGO complex electrode prepared by depositing the powder of the complex prepared using the one-step hydrothermal method and the post-thermal treatment on the nickel foam. This study discusses a rarely investigated subject and provides a blueprint for choosing the methodology to synthesize efficient electroactive material for the energy storage devices.